ANALISIS KEPUASAN PASIEN BPJS TERHADAP PELAYANAN KEPERAWATAN: STUDI KASUS DI RSUD. SYEKH YUSUF KABUPATEN GOWA - Liliskarlina, Liliskarlina; Mulyana, A saputri; Ekawaty, Dian (Universitas Islam Negeri Alauddin Makassar, 2019)
Nursing as an integral part of health services is an implication of nurses 'responsibility in serving patients' needs for 24 hours. The complexity of fulfilling the client's basic needs as the goal of nurse interaction with the client requires the nurse as the provider of nursing care to maximize their professionalism, including for the patients, user of BPJS Health. This study was conducted qualitatively with a phenomenological approach to understand the meaning of the experience of patients with BPJS on nursing services in Syekh Yusuf Hospital, Gowa Regency. The process of collecting data is done through in-depth interviews, document searches, and field observations. The results of this study was identified by 3 (three) themes, namely: Expect more caring and communicative nurse attitudes; caring attitude of nurses can make comfort and feeling heal faster; and Satisfied with the appropriate maintenance costs. This study recommends that further research can examine the cultural competence of nurses in hospitals. And to the nursing management at the Hospital, they can conduct a cultural awareness workshop to increase the cultural competence of nurses. Keywords: Caring; Nursing Care; Satisfaction ; Social Insurance Administration Organization